Ozone therapy in dentistry: A literature review - Vrinda Vats; Sonam Dhall; Akshat Sachdeva (Wolters Kluwer Medknow Publications, 2022)
Ozone is a form of oxygen which has shown to be fruitful in the management of various diseases for many years now. Ozone therapy is slowly emerging as an alternative treatment modality for many dental pathologies catering to all age groups. It has proven to be beneficial than conventional strategies with applications to dental treatment. The present article aims to discuss the role of ozone in the management of certain conditions in the oral cavity and its possible clinical applications in the future.